Cost of Serving Others: A Moderated Mediation Model of OCB, Ego Depletion, and Service Sabotage - Hongbo, Li; Waqas, Muhammad; Tariq, Hussain; Yahya, Farzan; Marfoh, Joseph; Ali, Ahsan; Ali, Syed Muhammad (Frontiers in Psychology, 2021)
Grounding on ego-depletion theory, this study highlights ego depletion as a mechanism that explains how employees’ organizational citizenship behavior (OCB) leads to antagonistic consequences i.e. service sabotage. Employees’ positive psychological capital (PsyCap) is theorized to moderate the hypothesized relationships investigated in this study. PROCESS macro developed by A. F. Hayes (2013) were used to test all the hypotheses by using time-lagged, dyadic data collected from 420 Chinese employees and 112 their supervisors associated with the service industry. This study finds that OCB seems to cause ego depletion on the part of employees resulting in service sabotage. It is concluded that employees’ exhibition of OCB is positively linked to ego depletion, which in turn drives service sabotage behavior. Furthermore, employees’ PsyCap weakens the effect of OCB on employees’ ego depletion. This study not only highlights the dark side of OCB, the mechanism through which it causes adverse effects, and the moderating effect of PsyCap but also provides insights to the organizations for managing service sector employees so that they can effectively interact with customers. Our findings suggested that employees with high PsyCap experience less ego depleted, thus, such measures are suggested which help to enhance employees’ PsyCap. We also suggest managers consider the same factor during the recruitment process.